Fibrosis-related gene expression in the prostate is modulated by doxazosin treatment - Delella, Flávia Karina [UNESP]; Lacorte, Livia M. [UNESP]; Almeida, Fernanda Losi A.; Dal Pai, Maeli [UNESP]; Felisbino, Sergio L. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Aims: To gain new insights into the molecular mechanisms of action of doxazosin, we investigated the prostatic stroma ultrastructure and the expression of genes involved with fibrosis, such as collagen type I and III (COL1A1 and COL3A1, respectively) and TGF-beta 1, in the rat ventral prostate.Main methods: Adult Wistar rats were treated with doxazosin (25 mg/kg/day), and the ventral prostates were excised at 7 and 30 days after treatment. Untreated rats were controls. Ventral prostates were subjected to ultrastructural, immunohistochemical, biochemical and molecular analyses.Key findings: Doxazosin-treated prostates showed thickened bundles of collagen fibrils, activated fibroblasts, enlarged neurotransmitter vesicles and increased tissue immunostaining for collagen type I and type III when compared to untreated prostates. After 7 and 30 days of doxazosin treatment mRNA expression of COL1A1 and COL3A1 was significantly increased and reduced, respectively, compared to the control group. TGF-beta 1 mRNA and protein levels were increased after 7 days of doxazosin treatment, whereas only mRNA levels remained increased after 30 days of treatment.Significance: Our data suggest that relaxation of smooth muscle cells by alpha-blockers interferes with the mechanical dynamics of the prostatic stroma extracellular matrix components, generating a pro-fibrotic effect probably via the TGF-beta 1 signaling pathway. Long term treatment with doxazosin may also lead to a reduced turnover of extracellular matrix components. Our results add to a better understanding of the molecular mechanisms behind the effects of alpha-blockade on prostatic histoarchitecture and the response to treatment for benign prostatic hyperplasia. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Doxazosin; Benign prostatic hyperplasia; Collagen; TGF beta-1; Alpha-adrenergic blockade; Neurotransmitter vesicles